Clinical outcomes with the LMWH, tinzaparin in pregnancy: an international retrospective audit. (16th November 2010) - Nelson-Piercy, C; Rodger, M; Powrie, R; Borg, JY; Greer, I
Abstract : Low molecular weight heparins are the anticoagulants of choice in pregnancy in current guidelines. The aim of this multinational retrospective audit was to gather data on maternal and fetal outcomes in consecutive pregnancies treated with tinzaparin. Use solely after delivery was excluded. Data were gathered from 1260 pregnancies comprising 254 venous thromboembolism (VTE) treatment (mean dose 12 840 IU/day for 85 days, 94.1% once-daily) and 1006 prophylaxis (6382 IU/day for 165 days, 94.6% once-daily) involving 1296 fetuses. There were 868 (70.4%) vaginal deliveries (76 assisted) and 365 (29.6%) Caesarean sections, (data missing for 27). Neuraxial anaesthesia was administered in 40.4% with no epidural haematomas reported. From the 1296 fetuses there were 1238 (95.5%) live births, 15 (1.2%) stillbirths, 40 (3.1%) spontaneous abortions and 3 (0.2%) pregnancy terminations. Blood loss at delivery was ≤500 ml in 914 (87.0%), 501–1500 ml in 126 (12.0%) and >1500 ml in 11 (1.0%) women (data missing for 209). There were no maternal deaths, six (0.5%) neonatal deaths (five births <27 weeks and one Ebstein's anomaly) and no neonatal haemorrhages. There were five (2.0%) recurrent VTEs in the treatment group and 10 (0.99%) in the prophylaxis group. Adjudicated safety outcomes are, at this time, only available for the UK/IE subset (656 pregnancies) where 60 cases of 'any bleeding' (9.1%) were adjudicated related to tinzaparin. Eight (1.2%) of these required medical intervention. Full final results for all 1260 pregnancies will be first available at the meeting. These results provide reassuring maternal and fetal outcome information in pregnancies exposed to tinzaparin.